2005
DOI: 10.1620/tjem.206.243
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link between Nickel Allergy and Coronary Stent Restenosis?

Abstract: NARIN, A. Is There a Link between Nickel Allergy and Coronary Stent Restenosis?Tohoku J. Exp. Med., 2005, 206 (3), [243][244][245][246] Although many patients with coronary artery disease are being treated by coronary stents, in-stent restenosis is the major limitation of percutaneous coronary stenting procedures. Most stents are made of stainless steel, and that, allergic reactions to nickel ions released from coronary stainless-steel stents may be one of the triggering mechanisms for in-stent restenosis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 8 publications
0
38
1
Order By: Relevance
“…The debate focused on nickel due to it being present at higher levels than molybdenum in 316L -nominally 12% compared to 2.5%, respectively. While the subject did fuel ongoing developments of inorganic stent coatings, to prevent ion release, subsequent studies have failed to establish an effect [20]. It is also worth noting that the introduction of cobaltchromium alloy stents was not impeded by the discussion; L605 contains 10% nickel while MP35N contains 35% nickel and 10% molybdenum.…”
Section: Metal Ion Release and Restenosismentioning
confidence: 99%
“…The debate focused on nickel due to it being present at higher levels than molybdenum in 316L -nominally 12% compared to 2.5%, respectively. While the subject did fuel ongoing developments of inorganic stent coatings, to prevent ion release, subsequent studies have failed to establish an effect [20]. It is also worth noting that the introduction of cobaltchromium alloy stents was not impeded by the discussion; L605 contains 10% nickel while MP35N contains 35% nickel and 10% molybdenum.…”
Section: Metal Ion Release and Restenosismentioning
confidence: 99%
“…A third study was excluded as it was actually an article investigating whether patients with a stent implanted have a higher risk of developing contact allergy [9]. Finally, nine studies [5,6,[10][11][12][13][14][15][16], including 1223 patients, were included in the meta-analysis. Table 1 shows the characteristics of all nine studies included in our analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Hillen et al [107] and Norgaz et al [108] reached the conclusion that pre-existing metal allergy should not be considered a risk factor for developing ISR, although they acknowledged that the small number of patients limited the study. Thyssen et al [109] performed an individual linkage study of 149 patients and found that nickel and/or chromium allergy in dermatitis patients does not appear to increase the overall risk of ISR after percutaneous coronary intervention.…”
Section: Intravascular Devicesmentioning
confidence: 99%